Target-Oriented Inversion of Time-Lapse Seismic Waveform Data (Communications in Computational Physics, 2020)
Full waveform inversion of time-lapse seismic data can be used as a meansof estimating the reservoir changes due to the production. Since the repeated computations for the monitor surveys lead to a large computational cost, time-lapse full waveform inversion is still considered to be a challenging task. To address this problem,we present an efficient target-oriented inversion scheme for time-lapse seismic datausing an integral equation formulation with Gaussian beam based Green's functionapproach. The proposed time-lapse approach allows one to perform a local inversionwithin a small region of interest (e.g. a reservoir under production) for the monitor survey. We have verified that the T-matrix approach is indeed naturally target-oriented,which was mentioned by Jakobsen and Ursin [24] and allows one to reduce the computational cost of time-lapse inversion by focusing the inversion on the target-area only.This method is based on a new version of the distorted Born iterative T-matrix inversescattering method. The Gaussian beam and T-matrix are used in this approach to perform the wavefield computation for the time-lapse inversion in the baseline modelfrom the survey surface to the target region. We have provided target-oriented inversion results of the synthetic time-lapse waveform data, which shows that the proposedscheme reduces the computational cost significantly.
Keywords: Waveform inversion; time-lapse seismic; seismic inverse scattering; target-oriented inversion; Gaussian beam based Green's function.